Assessing physical activity during youth sport: The observational system for recording activity in children: Youth sports - Cohen, A.; McDonald, S.; McIver, K.; Pate, R.; Trost, S. (Pediatric Exercise Science, 2014)
The purpose of this study was to evaluate the validity and interrater reliability of the Observational System for Recording Activity in Children: Youth Sports (OSRAC:YS). Children (N = 29) participating in a parks and recreation soccer program were observed during regularly scheduled practices. Physical activity (PA) intensity and contextual factors were recorded by momentary time-sampling procedures (10-second observe, 20-second record). Two observers simultaneously observed and recorded children`s PA intensity, practice context, social context, coach behavior, and coach proximity. Interrater reliability was based on agreement (Kappa) between the observer`s coding for each category, and the Intraclass Correlation Coefficient (ICC) for percent of time spent in MVPA. Validity was assessed by calculating the correlation between OSRAC:YS estimated and objectively measured MVPA. Kappa statistics for each category demonstrated substantial to almost perfect interobserver agreement (Kappa = 0.67-0.93). The ICC for percent time in MVPA was 0.76 (95% C.I. = 0.49-0.90). A significant correlation (r = .73) was observed for MVPA recorded by observation and MVPA measured via accelerometry. The results indicate the OSRAC:YS is a reliable and valid tool for measuring children`s PA and contextual factors during a youth soccer practice.